Hyperandrogenism as a clinical manifestation of familial partial lipodystrophy type 2 in an adolescent female patient - Błaszczyk, Ewa; Tobolska-Lorek, Dominika; Januszek-Trzciąkowska, Aleksandra; Karbowska, Dorota; Gawlik-Starzyk, Aneta (Pediatria Polska - Polish Journal of Paediatrics, 2025)
We present a case report of a girl with significant hyperandrogenism with accompanying metabolic disorders. In the physical examination, attention was drawn to tall stature, excessive body mass with a muscular build, broad shoulders and a narrow pelvis, low timbre of voice, acne lesions, enlarged mandible, hirsutism (19 points on the Ferriman-Gallwey scale), and elevated blood pressure. Substantial hyperandrogenemia was noted, with a significantly increased testosterone level and elevated levels of adrenal androgens. Based on steroid metabolome analysis from 24-hour urine collection, congenital adrenal hyperplasia was ruled out. Dyslipidemia and impaired glucose tolerance with hyperinsulinism in the oral glucose tolerance test were found. Magnetic resonance imaging of the abdomen and pelvis revealed a fatty liver and overgrowth of muscles and mesentery with adipose tissue. Whole exome sequencing was performed, revealing the presence of a known, pathogenic molecular variant, c.1394G > A, in the LMNA gene, associated with the occurrence of familial partial lipodystrophy.